2007
DOI: 10.1007/978-3-540-72586-2_116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Linux Scheduling with VAMPIR

Abstract: Abstract. Analyzing the scheduling behavior of an operating system becomes more and more interesting because multichip mainboards and Multi-Core CPUs are available for a wide variety of computer systems. Those system can range from a few CPU cores to thousands of cores. Up to now there is no tool available to visualize the scheduling behavior of a system running Linux. The Linux Kernel has an unique implementation of threads, each thread is treated as a process. In order to be able to analyze scheduling events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Kluge et al [19] developed a framework for monitoring the Linux scheduler called VAMPIR that observes the number of task movements in multi-processor environments. In a larger case study, they observed the schedulers load balancing behaviour for a MPI application in three different scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…Kluge et al [19] developed a framework for monitoring the Linux scheduler called VAMPIR that observes the number of task movements in multi-processor environments. In a larger case study, they observed the schedulers load balancing behaviour for a MPI application in three different scenarios.…”
Section: Related Workmentioning
confidence: 99%